Comparison of lateral entry and crossed entry pinning for pediatric supracondylar humeral fractures: a meta-analysis of randomized controlled trials - Huaguo Zhao; Song Xu; Guanyi Liu; Jingyu Zhao; Shandong Wu; Linrui Peng (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Closed reduction and pinning entry fixation have been proposed as treatment strategies for displaced supracondylar humeral fractures (SCHFs) in children. However, controversy exists regarding the selection of the appropriate procedure. Hence, this meta-analysis was conducted to compare the effect of lateral and crossed pin fixation for pediatric SCHFs, providing a reference for clinical treatment. Methods Online databases were systematically searched for randomized controlled trials (RCTs) comparing lateral pinning entry and crossed pinning entry for children with SCHFs. The primary endpoints were iatrogenic ulnar nerve injuries, complications, and radiographic and functional outcomes. Results Our results showed that iatrogenic ulnar nerve injuries occurred more commonly in the crossed pinning entry group than in the lateral pinning entry group (RR = 4.41, 95% CI 1.97–9.86, P < 0.05). However, its risk between the crossed pinning with mini-open incisions group and the lateral pinning entry group was not significantly different (RR = 1.58, 95% CI 0.008–29.57, P = 0.76). The loss of reduction risk was higher in the lateral pinning entry group than in the crossed pinning entry group (RR = 0.66; 95% CI 0.49–0.89, P < 0.05). There were no significant differences in the carry angle, Baumann angle, Flynn scores, infections, and other complications between these two groups. Conclusions The crossed pinning entry with mini-open incision technique reduced the loss of reduction risk, and the risk of iatrogenic ulnar nerve injury was lower than in the lateral pinning entry group. The crossed pinning entry with mini-open incision technique is an effective therapeutic strategy for managing displaced supracondylar humeral fractures in children.